Interfacing biology with nanoparticles - Mandal, Sujata; Phadtare, S.; Sastry, M. (Current Applied Physics, 2005)
New approaches are constantly being developed for both the synthesis of inorganic nanomaterials and their surface modification for sensing and electronic applications. Insofar as surface modification of gold nanoparticles is concerned, thiol chemistry is the most popular approach to bind ligands to their surface. We have been pursuing the possibility of using amine functionality to bind ligands to the surface of gold nanoparticles and have found that amine binding is as strong as thiol binding. The advantages of using amine chemistry for surface modification of nanogold are many, the possibility of complexing a large variety of biomolecules such as amino acids and proteins being one of the most important. In this article, we review the work from this laboratory on the stabilization of gold nanoparticles using amino acids as well as using amino acids as reducing agents to obtain stable aqueous solutions of gold nanoparticles of variable size. We also discuss the possibility of forming bioconjugates of enzymes with gold nanoparticles decorating the surface of polymer microspheres and their application as reusable biocatalysts. There is much to be gained by marrying nanomaterials with biology with considerable spin-offs likely in both nanotechnology and biotechnology. (C) 2004 Elsevier B.V. All rights reserved.
Indo-Japan Workshop on Advanced Molecular Electronics and Bionics, Kyushu Inst Technol, Grad Sch Life Sci & Syst Engn, Kitakyushu, JAPAN, DEC 11-13, 2003
Keywords: amino acids' enzyme immobilization; Nanoparticles; Proteins

Development of non-woven nanofibers of egg albumen-poly (vinyl alcohol) blends: influence of solution properties on morphology of nanofibers - Rathna, Gundloori Venkata Naga; Jog, Jyoti Prakash; Gaikwad, A. B. (Polymer Journal, 2011)
Egg albumen (EA), a highly functional globular protein with desirable properties, is the least-explored material for biomaterial applications, although it is available in abundance. In our studies, we explored the viability of EA and various blends with biocompatible and non-toxic poly (vinyl alcohol) (PVA) to produce nanofibers for biomedical applications. EA and PVA blends were prepared in various compositions. Electrospinning was used to fabricate non-woven nanofibers. Solution properties, such as viscosity and electrical conductivity, were evaluated for various prepared solutions. Solution viscosity increased with increasing polymer concentration. Solutions with higher contents of EA recorded increased conductivity, which decreased with increasing PVA content. The influence of solution properties on the morphological appearance of as-spun products was studied using scanning electron microscopy. Instead of nanofibers, nanoparticles and microparticles of EA were produced at even higher contents. In contrast, a gradual increase in the addition of PVA content to 8% EA solution resulted in the transformation of particles from large agglomerates to very fine fibers (approximate to 100nm in diameter) because of the influence of polymer content, viscosity and conductivity. The polymer-polymer interactions in the prepared materials have been validated by Fourier transform infrared spectroscopy, differential scanning calorimetry, X-ray diffraction and gel electrophoresis. Polymer Journal (2011) 43, 654-661; doi:10.1038/pj.2011.34; published online 18 May 2011
Keywords: Biocompatibility; biodegradable; blends; nanotechnology; Proteins

Investigation of C-C bond formation mediated by bombyx mori silk fibroin materials - Kuehbeck, Dennis; Ghosh, Munmun; Sen Gupta, Sayam; Diaz, David Diaz (ACS Sustainable Chemistry & Engineering, 2014)
The formation of C-C bonds is a prerequisite for all life on earth. Understanding the role of proteins in mediating the formation of these bonds is important for understanding biological mechanisms in evolution, as well as for designing ``green catalysts''. In this work, the ability of silk fibroin (SF) proteins to mediate selective C-C bond formation under mild conditions was comprehensively evaluated and compared between different SF-based materials and other proteins. Aqueous SF solution (ASFS), freeze-dried SF (FDSF), mesoporous SF (MPSF), and SF hydrogel (SFHG) materials were prepared and characterized by a variety of techniques including, among others, FE-SEM, ICP-OES, FT-IR, and TGA. The nitroaldol (Henry) reaction, Knoevenagel condensation, and direct aldol reaction were used as models for this study, in which the recovery and reusability of the protein was also evaluated.
Keywords: Aldol-like reactions; C-C Bond formation; Knoevenagel condensation; Proteins; Silk fibroin

Nature of selenium hydrogen bonding: gas phase spectroscopy and quantum chemistry calculations - Mishra, Kamal K.; Singh, Santosh K.; Ghosh, Paulami; Ghosh, Debashree; Das, Aloke (Physical chemistry Chemical physics, 2017)
<div class="block-record-info" style="margin: 0px 22px 22px; list-style: none; padding: 0px; line-height: 20px; font-size: 13px; color: rgb(51, 51, 51); font-family: arial, helvetica, sans-serif; background-color: rgb(248, 248, 248);"> Subsequent to the recent re-definition of hydrogen bonding by the IUPAC committee, there has been a growing search for finding the presence of this ever interesting non-covalent interaction between a hydrogen atom in an X-H group and any other atom in the periodic table. In recent gas phase experiments, it has been observed that hydrogen bonding interactions involving S and Se are of similar strength to those with an O atom. However, there is no clear explanation for the unusual strength of this interaction in the case of hydrogen bond acceptors which are not conventional electronegative atoms. In this work, we have explored the nature of Se hydrogen bonding by studying indole...dimethyl selenide (indmse) and phenol...dimethyl selenide (phdmse) complexes using gas phase IR spectroscopy and quantum chemistry calculations. We have found through various energy decomposition analysis (EDA) methods and natural bond orbital (NBO) calculations that, along with electrostatics and polarization, charge transfer interactions are important to understand Se/S hydrogen bonding and there is a delicate balance between the various interactions that plays the crucial role rather than a single component of the interaction energy. An in-depth understanding of this type of non-covalent interaction has immense significance in biology as amino acids containing S and Se are widely present in proteins and hence hydrogen bonding interactions involving S and Se atoms contribute to the folding of proteins.
Keywords: Center-Dot-O; Clusters; Co-Ordination; Complexes; intermolecular interactions; Proteins; Replacement; spectra; Strength; Sulfur

Surface modification of polymers for tissue engineering applications: arginine acts as a sticky protein equivalent for viable cell accommodation - Sengupta, Poulomi (ACS Omega, 2018)
Hydrophobic polymers, for their favorable mechanical properties, are a popular choice as permanent bioimplants. These materials remain absolutely bioinert for years, but throw up challenges when it comes to fast integration with healthy tissue. Addressing this, herein, we present a surface-modification technique of converting the hydrophobic surface of a polymeric film into a hydrophilic one using a layer-by-layer assembly process involving gold nanoparticles and small molecules like amino acids. These films showed much improved animal cell (murine fibroblast) adherence properties compared to commercially available tissue culture plates. Moreover, arginine-modified films exhibited a nearly equivalent cell viability compared to the films modified with the natural extracellular matrix component fibronectin. The surface hydrophilicity and roughness of our novel film were characterized by contact angle measurement and atomic force microscopy. Cell counting, fluorescence microscopy, cell viability, and collagen estimation assay were employed to demonstrate that our film favored a much improved cell adherence, and accommodation in comparison to the commercially available tissue culture plates.
Keywords: Cell and Molecular biology; Extracellular matrix proteins; Nanoparticles; Physical and chemical properties; Polymers; Proteins; Surface structure; Surface treatment; Thin films; tissue engineering

Synthesis of phospho-polypeptides via phosphate-containing N-carboxyanhydride: application in enzyme-induced self-assembly, and calcium carbonate mineralization - Mondal, Basudeb; Das, Soumen; Panda, Sidharth; Dutta, Tahiti; Sen Gupta, Sayam (ChemPlusChem, 2020)
An easy synthetic strategy was developed to synthesize the phosphate-functionalized amino acid N-carboxyanhydride (NCA), using simple primary amine initiators to obtain homo and block phospho-polypeptides with controlled molecular weight and molecular weight distribution. The methodology was extended to the synthesis of the end-functionalized homo polypeptides (15 to 50 repeat unit) and block co-polypeptides with PEG (0.7 K, 2 K, and 5 K) and glycopolypeptide (15-unit mannose glycopolypeptide) as one of the blocks. The deprotected fully water-soluble anionic phosphate-based polypeptides showed pH-dependent helical conformation with a helical content of 20 %, which further changed to beta-sheets upon addition of the enzyme alkaline phosphatase (ALP) due to dephosphorylation. The block co-polypeptide containing PEG as one of the blocks led to its self-assembly into colloidal structures, such as vesicles with a hydrodynamic diameter of similar to 250 nm, due to the formation of amphiphilic block co-polymer upon dephosphorylation. The nature of the colloidal structures formed can be temporally controlled by the extent of dephosphorylation. Finally, the phospho-polypeptides serve as a template for the mineralization of calcium carbonate with varying polymorphs and morphologies.
Keywords: Biomineralization; enzymes; phosphopolypeptides; Proteins; Self-assembly